عقود المالية الإسلامية وتطبيقاتها بالمغرب في ضوء أصول المذهب المالكي - Lahjouji, Hamza (İstanbul Sabahattin Zaim Üniversitesi, Sosyal Bilimler Enstitüsü, İslam İktisadı ve Hukuku Anabilim Dalı, 2019)
تهدف هذه الدراسة إلى تحليل عقود المالية التشاركية في المغرب في ضوء المذهب المالكي وأصوله لمعرفة مدى موافقة مواصفات عقود المالية التشاركية الصادرة عن بنك المغرب لاجتهادات المذهب المالكي وأصوله، بحيث تناولت الدراسة المالية التشاركية في المغرب والمؤسسات الإشرافية عليها، أ وصول المذهب المالكي، ثم عقود التمويل التشاركي المعتمدة من قبل بنك المغرب والمجلس العلمي الأعلى ومدى مطابقتها لأصول المذهب المالكي وهي: عقد المرابحة للآمر بالشراء، عقد الإجارة المنتهية بالتمليك، عقد المشاركة، عقد المضاربة وعقد السلم. ولتحقيق أهداف البحث تم اتباع المنهج الاستقرائي باستقراء عقود المالية التشاركية المطبقة في البنوك التشاركية في المغرب، ثم المنهج الوصفي في وصف أهم العقود التي اعتمدها بنك المغرب مع ذكر طرق استخدامها وأوصافها التقنية، والمنهج المقارن؛ من خلال مقارنة العقود المعتمدة من قبل بنك المغرب والمجلس العلمي الأعلى والعقود التي ذكرت في المذهب المالكي مع بيان مدى مطابقتهما لبعضهما، وأخيرا المنهج التحليلي؛ من خلال تحليل عقود المالية التشاركية في المغرب في ضوء أصول المذهب المالكي. وتوصلت الدراسة إلى مجموعة من النتائج منها: أن العقود التي أصدرها بنك المغرب بشكل عام موافقة للمذهب المالكي إلا أنه في بعض المسائل الفقهية تم الأخذ برأي المذاهب الفقهية الأخرى التي جاءت في ثنايا البحث كمسألة هامش الجدية الذي يدفعه العميل للبنك قبل توقيع العقود، وكيفية تحديد مبلغ تعويض الضرر هل يكون بمقدار ما لحق بالبنك أم أكثر، وإمكانية فسخ عقد الإجارة تلقائيا بدون سبب، وعدم النص على إمكانية إرجاع المسلم فيه إلى البائع خلال ثلاثة أيام فما دون ذلك، كما لم ينص على أن السلم لا يجري في المنافع، وغيرها من القضايا.

This study intends to examine the Islamic financial contracts in Morocco in the light of Al-Maliki School of Fiqh, in order to investigate to what extent those contracts are complying with the specifications that have been set by Bank Al-Maghrib and the jurisprudence of Al-Maliki School. These include: Murabaha Lil Amir Bialshira, Ijarah Muntahia Bittamleek (Leasing) contract, Musharakah contract, Mudarabah contract, and Al-Salam contract. In order to achieve the objectives of the research, it was more appropriate to follow the descriptive approach in a way to interpret the most important contracts that have been approved by Bank Al-Maghrib including how those contracts are being practiced, explaining their technical descriptions; and the comparative approach. through comparing the contracts that are approved by Bank Al-Maghrib and the Higher Scientific Council, and the contracts that are mentioned in the Maliki School of Fiqh, in order to reveal the extent of compliance. Finally the analytical approach was used through the analysis of participatory financial contracts in Morocco in light of Al-Maliki School of Fiqh. This study has reached a number of results, including the contracts issued and approved by Bank Al-Maghrib, in general, are complying with the contract of Al-Malki School of Fiqh. However some jurisprudential issues were basedon the opinion of other schools of jurisprudence. For example, the matter of the margin of seriousness (Hamish al-jiddiyyah) paid by the client to the bank before signing contracts, and how to determine the amount of compensation for the damage and whether the compensation equal to amount of damage to the bank or more, Another issue is that the possibility to terminate Al-Ijarah contract automatically for no reason, Whereas in case of Salam contract regarding returning Al-Musalam Fihi to the seller within three days this is what this school of Fiqh has stated. Also, the Maliki school of Fiqh Stated that Al-Salam contract is not being made on the benefit, and other issues.

Bu çalışmanın hedefi; Fas Bankasındaki İslamî finansman sözleşmelerini, Mâliki mezhebi ve usulü ışığında incelemek ve mezhebin içtihat kurallarına uyma durumunu tespit etmek. Dolayısıyla bu çalışmada Mâliki mezhebinin usulü ve katılım bankalarını denetleyen kurumların belirlediği kriterler, daha sonra Fas Bankası ve Yüksek İlmi Kurumu tarafından kabul edilen finansman sözleşmeleri incelenmiştir. Sözü geçen bu sözleşmeler: murabaha, temlikle sonuçlanan kiralama, ortaklık, mudârebe ve selem sözleşmeleridir. Bu çalışmada kullanılan yöntem ve yaklaşımlar ise; tanımlama, karşılaştırma ve analiz etme yaklaşımlarıdır. Bu yaklaşımlar ile Fas Bankasının kabul ettiği sözleşmeleri ve bu sözleşmelerin kullanış ve özelliklerini tanımlamaya, Fas Bankası ve Yüksek İlmi Kurumu tarafından kabul edilen finansman sözleşmelerinin Mâliki mezhebinin caiz gördüğü sözleşmeler ile karşılaştırmaya ve uygun olup olmadığını tespit etmeye, Mâliki mezhebi ışığında Fas’taki ortaklık sözleşmeleri analiz edilmeye çalışılmıştır. Çalışmanın sonunda elde edilen sonuç ise Fas Bankasının icra ettiği İslamî finansman sözleşmeleri, bazı fıkhi meseleler dışında genel olarak Mâliki mezhebin usulü ve kurallarına uygundur. Bu meselelerde diğer fıkhi mezheplere de başvurulmuştur. Böylece sözleşmeyi imzalamadan önce müşterinin bankaya ödediği güvence bedeli ve çekilme halinde zararı karşılamak için cezanın miktarını belirleme; sadece bankanın uğradığı zarar miktarınca mı yoksa daha fazla mı olacağı meselesi, kira sözleşmesini sebepsiz iptal etme imkânı meselesi, selem sözleşmelerinde satılan malın üç gün içerisinde iade imkânından bahsedilmemesi ve menfaatlerde selemin caiz olmadığından bahsedilmemesi örnek olarak verilmiştir.
The participative finance contracts in morrocco and their applications in the light of the maliki jurisprudence school
İslami finans sözleşmeleri ve bunların maliki mezhebine göre Fas'taki uygulamaları
Keywords: عقود المالية التشاركية; المذهب المالكي; أصول المذهب; المرابحة للآمر بالشراء; الإجارة المنتهية بالتمليك; المشاركة; المضاربة، السلم; Participatory finance contracts; Al-Maliki school; Origins of school; Murabahah to The Purchase Orderer (MPO); Ijarah muntahah bittamleek; Musharaka; Mudaraba; Salam; Katılım finansman sözleşmeleri; Mâliki mezhebi; Mezhebin usulü; Murabaha; Temlikle sonuçlanan kiralama; Ortaklık; Mudârebe; Selem